Copper-potassium-containing activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide and preparation method of copper-potassium-containing activated carbon adsorbent
By adding copper and potassium to the charcoal powder, and using specific preparation and regeneration methods, a recycled use of copper -potassium -containing carbon suction agent is prepared, which solves the problem of waste liquid treatment during the activated carbon regeneration process, and achieves high efficiency. Hydrogen sulfide adsorption and activated carbon regeneration.
Patent Information
- Application Number
- CN202411648012.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing activated carbon adsorbents are difficult to regenerate after adsorption saturation, resulting in waste of resources and increased carbon emissions, and traditional regeneration methods have problems with waste liquid treatment.
By directly adding copper and potassium elements to the carbon powder, adding oxalic acid and ammonium humate during the preparation process, and using a specific ratio of nitrogen to water vapor for high-temperature activation treatment, a recyclable copper-containing potassium activated carbon adsorption was prepared agent. This method produces no waste liquid during the preparation and regeneration process, and the regeneration operation is simple.
The adsorption capacity of activated carbon for hydrogen sulfide is increased, the activation temperature is lowered, the mechanical strength is enhanced, and the specific surface area is increased through specific atmosphere treatment to ensure that the regenerated activated carbon maintains excellent adsorption performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of activated carbon adsorbent regeneration, and in particular to a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide and a preparation method thereof. Background Art
[0002] Activated carbon adsorbents are widely used to remove low-concentration hydrogen sulfide, such as blast furnace gas, coke oven gas and oil field associated gas. However, currently activated carbon adsorbents are mostly used once, and the activated carbon saturated with adsorption is often simply treated as fuel by sintering, resulting in waste of activated carbon and increased carbon emissions.
[0003] Research on recyclable activated carbon adsorption has also begun to attract the attention of researchers. For example, Chinese patents CN202322235551 and CN202311047511 disclose a blast furnace gas desulfurization activated carbon regeneration process and device, which can promote the regeneration of activated carbon through washing extraction, heating regeneration and other methods. However, this method contains a washing and extraction process, and there is still the problem of waste liquid reprocessing. Summary of the invention
[0004] In view of the problems existing in the regeneration of activated carbon in the prior art, the present invention starts from the source of preparing activated carbon and provides a copper-potassium activated carbon adsorbent that can recycle hydrogen sulfide and a preparation method thereof. Compared with the traditional preparation of copper-containing activated carbon adsorption, the copper-potassium activated carbon prepared by the present invention does not generate any waste liquid during the preparation and regeneration processes, and the regeneration operation is simple. The regenerated activated carbon still exhibits excellent adsorption performance.
[0005] The present invention adopts the following technical solution:
[0006] A copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide is prepared from the following raw materials in parts by weight:
[0007]
[0008] Preferably, the copper-potassium activated carbon adsorbent is prepared from the following raw materials in parts by weight:
[0009]
[0010] The carbon powder is fine carbon powder particles with a mesh size between 200 and 400 meshes.
[0011] The copper salt is one or more of copper sulfate, copper nitrate, copper chloride and copper acetate.
[0012] The potassium salt is one or more of potassium sulfate, potassium nitrate, potassium chloride and potassium carbonate.
[0013] A method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide comprises the following steps:
[0014] S1. Weigh each component according to the specified mass ratio and set aside;
[0015] S2, dissolving copper salt and potassium salt in deionized water, then adding oxalic acid and ammonium humate, and stirring evenly to obtain a mixed solution A;
[0016] S3, add carbon powder to the kneader, start the kneader to stir, and then slowly add the mixed solution A. After the addition is complete, continue kneading for 2 to 24 hours to obtain sample B;
[0017] S4, placing the kneaded sample B into an extruder for repeated extrusion molding for more than 5 times, placing the molded strip sample at room temperature for 12 to 24 hours, and then placing it in an oven at 110° C. for drying for 12 to 24 hours to obtain a dried sample C;
[0018] S5. Finally, the dried sample C is placed in a rotary kiln and subjected to high-temperature activation treatment in a mixed atmosphere of nitrogen and water vapor for 3 to 12 hours to obtain an activated carbon adsorbent containing copper and potassium.
[0019] The volume ratio of nitrogen and water vapor added in step S5 is (3-5):1, and the temperature of the water vapor is 120-170°C.
[0020] The high temperature activation temperature in step S5 is 500-700°C.
[0021] A copper-potassium activated carbon adsorbent or a copper-potassium activated carbon adsorbent prepared by a preparation method thereof is used for regeneration in hydrogen sulfide adsorption. The hydrogen sulfide adsorption atmosphere of the copper-potassium activated carbon adsorbent is: H2S content is 500-1000ppm, CO content is 25-28%, CO2 content is 10-15%, O2 content is 0.1-0.5%, water vapor content is 0-5%, and the rest is nitrogen; the copper-potassium activated carbon adsorbent is used at an air velocity of 2000-5000h -1 .
[0022] The regeneration condition of the copper-potassium activated carbon adsorbent is as follows: the copper-potassium activated carbon adsorbent is treated in a gas without hydrogen sulfide at 180 to 220° C. for 5 to 20 hours.
[0023] The technical solution of the present invention has the following advantages:
[0024] A. The present invention starts from the source of preparing activated carbon and directly adds copper and potassium elements to carbon powder, which on the one hand increases the adsorption capacity of activated carbon to sulfur sulfide and on the other hand effectively reduces the temperature required for the activation of activated carbon; oxalic acid and humic acid ammonia are added to enhance the mechanical strength of activated carbon; and the specific surface area of activated carbon is increased by a specific nitrogen to water vapor ratio.
[0025] B. Compared with the traditional preparation of copper-containing activated carbon adsorption, the copper-potassium activated carbon adsorbent prepared by the present invention does not generate any waste liquid during the preparation and regeneration process, and the regeneration operation is simple. The regenerated activated carbon still shows excellent adsorption performance. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] This embodiment provides a method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, comprising the following steps:
[0029] S1. Dissolve 10.6 g of copper nitrate and 8.3 g of potassium chloride in 20.0 g of deionized water, then add 5.2 g of oxalic acid and 7.8 g of ammonium humate, stir evenly, and set aside;
[0030] S2, put 100.0g, 300 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 6 hours;
[0031] S3, putting the kneaded sample into an extruder for repeated extrusion molding 6 times, leaving the molded strip sample at room temperature for 15 hours, and then placing it in an oven at 110°C for drying for 12 hours;
[0032] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 5 L / min nitrogen and 1 L / min water vapor was introduced, and the temperature was raised to 600 °C at a rate of 5 °C / min. After maintaining for 6 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1128 m 2 / g.
[0033] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 500ppm, CO content is 25%, CO2 content is 15%, O2 content is 0.2%, water vapor content is 2.0%, and the rest is nitrogen; the adsorbent is used at a space velocity of 2000h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 6.9%.
[0034] The conditions for adsorbent regeneration are: after the adsorbent is treated at 180°C for 10 hours in the above-mentioned hydrogen sulfide-free atmosphere, the temperature is lowered to room temperature to obtain a regenerated activated carbon adsorbent. The hydrogen sulfide adsorption performance is tested, and the results after such a cycle are shown in the following table:
[0035] Table 1 Adsorption performance of the samples of Example 1 for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide)
[0036] frequency 1 2 3 4 5 6 7 8 Sulfur Capacity 6.8% 6.9% 6.8% 6.7% 6.9% 6.9% 6.8% 6.9%
[0037] Embodiment 2:
[0038] This embodiment provides a method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, comprising the following steps:
[0039] S1. Dissolve 22.0 g of copper sulfate and 15.2 g of potassium nitrate in 50.0 g of deionized water, then add 14.6 g of oxalic acid and 16.2 g of ammonium humate, stir well, and set aside;
[0040] S2, put 200.0g, 200 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 8 hours;
[0041] S3, placing the kneaded sample into an extruder for repeated extrusion molding 8 times, placing the molded strip sample at room temperature for 12 hours, and then placing it in an oven at 110°C for drying for 15 hours;
[0042] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 6L / min nitrogen and 2L / min water vapor was introduced, and the temperature was raised to 650°C at a rate of 5°C / min. After maintaining for 4 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1241m 2 / g.
[0043] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 700ppm, CO content is 26%, CO2 content is 12%, O2 content is 0.1%, water vapor content is 3.0%, and the rest is nitrogen; the adsorbent is used at a space velocity of 3500h -1The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.3%.
[0044] The conditions for adsorbent regeneration are: after the adsorbent is treated at 190°C for 15 hours in the above-mentioned hydrogen sulfide-free atmosphere, the temperature is lowered to room temperature to obtain a regenerated activated carbon adsorbent. The hydrogen sulfide adsorption performance is tested, and the results after such a cycle are shown in the following table:
[0045] Table 2 Adsorption performance of the samples of Example 2 for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide)
[0046]
[0047]
[0048] Embodiment 3:
[0049] S1. Dissolve 16.3 g of copper chloride and 10.5 g of potassium carbonate in 35.0 g of deionized water, then add 12.8 g of oxalic acid and 18.0 g of ammonium humate, stir evenly, and set aside;
[0050] S2, put 150.0g, 400 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 12 hours;
[0051] S3, placing the kneaded sample into an extruder for repeated extrusion molding 6 times, placing the molded strip sample at room temperature for 10 hours, and then placing it in an oven at 110°C for drying for 20 hours;
[0052] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 8 L / min nitrogen and 2 L / min water vapor was introduced, and the temperature was raised to 700 °C at a rate of 5 °C / min. After maintaining for 10 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1352 m 2 / g.
[0053] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 1000ppm, CO content is 28%, CO2 content is 15%, O2 content is 0.3%, water vapor content is 4.5%, and the rest is nitrogen; the adsorbent is used at a space velocity of 5000h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.9%.
[0054] The conditions for adsorbent regeneration are: after the adsorbent is treated at 220°C in the above-mentioned hydrogen sulfide-free atmosphere for 8 hours, the temperature is lowered to room temperature to obtain a regenerated activated carbon adsorbent. The hydrogen sulfide adsorption performance is tested, and the results after such a cycle are shown in the following table:
[0055] Table 3 Adsorption performance of samples in Example 3 for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide)
[0056] frequency 1 2 3 4 5 6 7 8 Sulfur Capacity 7.9% 8.0% 7.9% 7.8% 8.1% 8.0% 8.0% 7.9%
[0057] Embodiment 4:
[0058] This embodiment provides a method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, comprising the following steps:
[0059] S1. Dissolve 30g of copper nitrate and 1g of potassium chloride in 30g of deionized water, then add 10g of oxalic acid and 5g of ammonium humate, stir well, and set aside;
[0060] S2, put 100.0g, 400 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 2 hours;
[0061] S3, placing the kneaded sample into an extruder for repeated extrusion molding 6 times, placing the molded strip sample at room temperature for 24 hours, and then placing it in an oven at 110°C for drying for 24 hours;
[0062] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 4 L / min nitrogen and 1 L / min water vapor was introduced, and the temperature was raised to 500 °C at a rate of 5 °C / min. After maintaining for 3 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1120 m 2 / g.
[0063] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 600ppm, CO content is 27%, CO2 content is 10%, O2 content is 0.4%, water vapor content is 1.0%, and the rest is nitrogen; the adsorbent is used at a space velocity of 3000h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.0%.
[0064] The conditions for regenerating the adsorbent are as follows: after treating the adsorbent in the above-mentioned hydrogen sulfide-free atmosphere at 200° C. for 20 hours, cooling it to room temperature to obtain a regenerated activated carbon adsorbent.
[0065] Embodiment 5:
[0066] This embodiment provides a method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, comprising the following steps:
[0067] S1. Dissolve 1g of copper sulfate and 30g of potassium nitrate in 10g of deionized water, then add 1g of oxalic acid and 10g of ammonium humate, stir evenly, and set aside;
[0068] S2, put 100.0g, 200 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 24 hours;
[0069] S3, placing the kneaded sample into an extruder for repeated extrusion molding 7 times, placing the molded strip sample at room temperature for 12 hours, and then placing it in an oven at 110°C for drying for 18 hours;
[0070] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 6L / min nitrogen and 2L / min water vapor was introduced, and the temperature was raised to 550°C at a rate of 5°C / min. After maintaining for 12 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1252m 2 / g.
[0071] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 900ppm, CO content is 26%, CO2 content is 14%, O2 content is 0.5%, water vapor content is 5.0%, and the rest is nitrogen; the adsorbent is used at a space velocity of 4500h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.1%.
[0072] The conditions for regenerating the adsorbent are as follows: after treating the adsorbent at 210° C. for 5 hours in the above-mentioned hydrogen sulfide-free atmosphere, cooling it to room temperature to obtain a regenerated activated carbon adsorbent.
[0073] Embodiment 6:
[0074] This embodiment provides a method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, comprising the following steps:
[0075] S1. Dissolve 25g of copper sulfate and 10g of potassium nitrate in 25g of deionized water, then add 5g of oxalic acid and 8g of ammonium humate, stir well, and set aside;
[0076] S2, put 100g, 200 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 8 hours;
[0077] S3, placing the kneaded sample into an extruder for repeated extrusion molding 8 times, placing the molded strip sample at room temperature for 12 hours, and then placing it in an oven at 110°C for drying for 15 hours;
[0078] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 6L / min nitrogen and 2L / min water vapor was introduced, and the temperature was raised to 650°C at a rate of 5°C / min. After maintaining for 4 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1241m 2 / g.
[0079] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 700ppm, CO content is 26%, CO2 content is 12%, O2 content is 0.1%, water vapor content is 3.0%, and the rest is nitrogen; the adsorbent is used at a space velocity of 3500h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.4%.
[0080] The conditions for adsorbent regeneration are: after the adsorbent is treated at 190°C for 15 hours in the above-mentioned hydrogen sulfide-free atmosphere, the temperature is lowered to room temperature to obtain a regenerated activated carbon adsorbent. The hydrogen sulfide adsorption performance is tested, and the results after such a cycle are shown in the following table:
[0081] Table 4 Adsorption performance of the samples of Example 6 for hydrogen sulfide (based on the penetration sulfur capacity of 5% hydrogen sulfide)
[0082] frequency 1 2 3 4 5 6 7 8 Sulfur Capacity 7.3% 7.3% 7.5% 7.6% 7.2% 7.3% 7.5% 7.5%
[0083] Embodiment 7:
[0084] S1. Dissolve 10g of copper chloride and 25g of potassium carbonate in 15g of deionized water, then add 7g of oxalic acid and 6g of ammonium humate, stir well, and set aside;
[0085] S2, put 100g, 400 mesh carbon powder into a kneader, start the kneader to stir, slowly add the above solution, after adding, continue kneading for 12 hours;
[0086] S3, placing the kneaded sample into an extruder for repeated extrusion molding 6 times, placing the molded strip sample at room temperature for 10 hours, and then placing it in an oven at 110°C for drying for 20 hours;
[0087] S4. Finally, the dried sample was placed in a rotary kiln, and a mixed atmosphere of 8 L / min nitrogen and 2 L / min water vapor was introduced, and the temperature was raised to 700 °C at a rate of 5 °C / min. After maintaining for 10 hours, the water vapor was turned off and the temperature was lowered to room temperature to obtain an activated carbon adsorbent containing copper and potassium. The specific surface area was measured to be 1352 m 2 / g.
[0088] Adsorption performance test: The hydrogen sulfide adsorption atmosphere of the adsorbent is: H2S content is 1000ppm, CO content is 28%, CO2 content is 15%, O2 content is 0.3%, water vapor content is 4.5%, and the rest is nitrogen; the adsorbent is used at a space velocity of 5000h -1 The adsorption performance of the adsorbent for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide) is about 7.7%.
[0089] The conditions for adsorbent regeneration are: after the adsorbent is treated at 220°C in the above-mentioned hydrogen sulfide-free atmosphere for 8 hours, the temperature is lowered to room temperature to obtain a regenerated activated carbon adsorbent. The hydrogen sulfide adsorption performance is tested, and the results after such a cycle are shown in the following table:
[0090] Table 5 Adsorption performance of the samples of Example 7 for hydrogen sulfide (based on the breakthrough sulfur capacity of 5% hydrogen sulfide)
[0091] frequency 1 2 3 4 5 6 7 8 Sulfur Capacity 7.8% 7.7% 7.9% 7.7% 7.5% 7.6% 7.6% 7.9%
[0092] The present invention starts from the source of preparing activated carbon, directly adds copper and potassium elements to carbon powder, on the one hand, increases the adsorption amount of activated carbon to sulfur sulfide, and on the other hand, effectively reduces the temperature required for the activation of activated carbon; adds oxalic acid and humic acid ammonia to enhance the mechanical strength of activated carbon; and increases the specific surface area of activated carbon through a specific nitrogen to water vapor ratio. In addition, compared with the traditional preparation of copper-containing activated carbon adsorption, the copper-potassium activated carbon prepared by the present invention does not generate waste liquid during the preparation and regeneration process, and the regeneration operation is simple, and the regenerated activated carbon still exhibits excellent adsorption performance.
[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, characterized in that: It is prepared from the following raw materials in parts by weight:
2. The copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight:
3. The copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide according to claim 1, characterized in that: The carbon powder is fine carbon powder particles with a mesh size between 200 and 400 meshes.
4. The copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide according to claim 1, characterized in that: The copper salt is one or more of copper sulfate, copper nitrate, copper chloride and copper acetate.
5. The copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide according to claim 1, characterized in that: The potassium salt is one or more of potassium sulfate, potassium nitrate, potassium chloride and potassium carbonate.
6. A method for preparing a copper-potassium activated carbon adsorbent capable of cyclically adsorbing hydrogen sulfide, characterized in that: The following steps are involved: S1. Weigh each component according to the specified mass ratio and set aside; S2, dissolving copper salt and potassium salt in deionized water, then adding oxalic acid and ammonium humate, and stirring evenly to obtain a mixed solution A; S3, add carbon powder to the kneader, start the kneader to stir, and then slowly add the mixed solution A. After the addition is complete, continue kneading for 2 to 24 hours to obtain sample B; S4, placing the kneaded sample B into an extruder for repeated extrusion molding for more than 5 times, placing the molded strip sample at room temperature for 12 to 24 hours, and then placing it in an oven at 110° C. for drying for 12 to 24 hours to obtain a dried sample C; S5. Finally, the dried sample C is placed in a rotary kiln and subjected to high-temperature activation treatment in a mixed atmosphere of nitrogen and water vapor for 3 to 12 hours to obtain an activated carbon adsorbent containing copper and potassium.
7. The preparation method according to claim 6, characterized in that: The volume ratio of nitrogen and water vapor added in step S5 is (3-5):1, and the temperature of the water vapor is 120-170°C.
8. The preparation method according to claim 7, characterized in that: The high temperature activation temperature in step S5 is 500-700°C.
9. The regeneration use of the copper-potassium activated carbon adsorbent or the copper-potassium activated carbon adsorbent obtained by the preparation method according to any one of claims 1 to 8 in the adsorption of hydrogen sulfide, characterized in that: The hydrogen sulfide adsorption atmosphere of the copper-potassium activated carbon adsorbent is: H2S content is 500-1000ppm, CO content is 25-28%, CO2 content is 10-15%, O2 content is 0.1-0.5%, water vapor content is 0-5%, and the rest is nitrogen; the use space velocity of the copper-potassium activated carbon adsorbent is 2000-5000h -1 .
10. The regeneration application according to claim 9, characterized in that: The regeneration condition of the copper-potassium activated carbon adsorbent is as follows: the copper-potassium activated carbon adsorbent is treated in a gas without hydrogen sulfide at 180 to 220° C. for 5 to 20 hours.
Citation Information
Patent Citations
A blast furnace gas desulfurization activated carbon regeneration process and device
CN116809045B
Blast furnace gas desulfurization activated carbon regeneration device
CN220371053U
Shaped coal-based SO2 and NO adsorption catalyst and preparation method thereof
CN102085476A
Composite material as well as preparation method and application thereof
CN112642397A
Sludge-based activated carbon, preparation method thereof and application of sludge-based activated carbon in adsorption of organic matters in wastewater
CN115676823A